Myocardial protection with glucose-insulin potassium in patients with acute coronary syndromes requiring coronary artery bypass grafting: A case series - Ellenberger, Christoph; Hagerman, Andres; Putzu, Alessandro; Cikirikcioglu, Mustafa; Licker, Marc (Frontiers in Anesthesiology, 2022)
Emergent cardiac surgery in patients with acute coronary syndrome (ACS) is always a challenging task for surgeons, anesthesiologists and patients. As “time is muscle”, early revascularization by percutaneous coronary intervention (PCI) has been largely advocated to salvage myocardial ischemic cells. In cases judged not suitable for PCI, on-pump coronary artery bypass grafting (CABG) is indicated with cardioplegic arrest and eventually anesthetic preconditioning to enhance myocardial protection. In these high-risk emergent procedures, adjuvant interventions could be implemented to the usual cardioprotective protocol to enhanced cardiac functional recovery. Although the infusion of glucose-insulin-potassium (GIK) has demonstrated interesting cardioprotective effects in animal models of myocardial ischemia and in patients undergoing elective cardiac surgery, this cardioprotective strategy has not yet been adopted largely. This case series describes the effects of GIK on left ventricular performance assessed by transesophageal echocardiography in four patients with ACS who required emergent CABG surgery.